2021
DOI: 10.1007/s11433-021-1724-6
|View full text |Cite
|
Sign up to set email alerts
|

NANOGrav results and dark first order phase transitions

Abstract: We show that the recent detection of a gravitational wave (GW) background reported by various pulsar timing array (PTA) collaborations including NANOGrav-15yr, PPTA, EPTA, and CPTA can be explained in terms of first order phase transitions (FOPTs) from dark sector models (DSM). Specifically, we explore a model for first order phase transitions that involves the majoron, a Nambu-Goldstone boson that is emerging from the spontaneous symmetry breaking of a U (1)L or U (1)B−L symmetry. We show how the predicted GW… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 97 publications
(67 reference statements)
0
39
0
Order By: Relevance
“…It is important to note that the induced GWs are not the only explanations of the NANOGrav results. For example, among many others, possible candidates are cosmic strings [328][329][330][331] and first order phase transitions [332][333][334][335][336][337][338][339]. Within the next decades, we expect to have more information from PTA experiments.…”
Section: Current and Future Observational Prospectsmentioning
confidence: 99%
“…It is important to note that the induced GWs are not the only explanations of the NANOGrav results. For example, among many others, possible candidates are cosmic strings [328][329][330][331] and first order phase transitions [332][333][334][335][336][337][338][339]. Within the next decades, we expect to have more information from PTA experiments.…”
Section: Current and Future Observational Prospectsmentioning
confidence: 99%
“…The differences in the predictions of m h φ and θ from the previous analysis solely originate from the numerical factor 0.28 in Eq. (12). The current maximally critical model tends to predict a slightly larger mass of h φ compared with the previous one.…”
Section: Modelmentioning
confidence: 67%
“…Gravitational Wave (GW) astronomy [1,2,3] is one of the most fascinating research fields because it allows us to explore the physics of the early universe, complementary to the cosmic microwave background (CMB) observations. Gravitational waves from compact binaries [4,5,6] and stochastic background [7,8,9,10,11,12] allow us to test new physics models as well as gravity theories. In particular, stochastic GWs originating from first-order phase transitions (FOPTs) [13,14,15,16] have received much attention in recent years, as many new physics models predict them in the early Universe, contrary to the pure Standard Model (SM), which shows a crossover electroweak (EW) transition [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, evidence for a commonspectrum process, which might be interpreted as a stochastic GW background (see e.g. [3][4][5][6][7][8][9][10][11][12][13] for related studies, see also [14][15][16]), was reported by the North American Nanohertz Observatory for Gravitational Waves (NANOGrav) collaboration in their 12.5-year dataset [17] and also reported later by the Parkes Pulsar Timing Array (PPTA) collaboration [18].…”
Section: Introductionmentioning
confidence: 99%